Meta-analysis of the effect of percutaneous coronary intervention on chronic total coronary occlusions - Li, Ruogu (BioMed Central, 2014)
BACKGROUND AND PURPOSE: Coronary chronic total occlusion (CTO) is the last stage of coronary artery atherosclerosis. Percutaneous coronary intervention (PCI) is a therapeutic procedure used to recanalize vessels with total occlusion. However, successful recanalization of CTO is still not optimal, and the key influence factors are still uncertainty. Therefore, a scientific evaluation on the effective of PCI for CTO treatment is necessary. METHODS: Relevant studies of PCI treatment for CTO were examined. Data were extracted and assessed by two independent clinical experts. Embase, PubMed and Medline et al. were used as database. The main research key words include “CTO”, “PCI”, “Stent”, “Reopen”, “long-term”, “follow-up” and “outcome”. Quality assessment was carried out according to the Cochrane Handbook. The selected data were pooled and analyzed using fixed-effect model and random-effect model. Heterogeneity was assessed using the I(2) test, Q test, L’abbe and Galbraith. Comprehensive Meta -Analysis 2.0 and Metanalysis 1.0 were used for statistics analysis in this research. RESULTS: A total of 16 articles involving 6695 cases in successful CTO recanalization (CTO success group) and 2370 cases in failed CTO recanalization(CTO failure group) were included in this research. Low CTO success was associated with elder age, previous coronary artery bypass graft surgery (CABG) history, multi-vessel diseases and right coronary artery disease lesion. Six follow-up variables including major adverse cardiac events (MACE), recurrent myocardial infarction (MI), all-cause death, incidence of angina, subsequent CABG and cumulative survival rate were found significantly reduced associated with CTO success. CONCLUSIONS: Clinical baseline characteristics such as age, previous CABG history and lesion baseline characteristics such as lesion length, multi-vessel diseases might be important factors influencing the successful rate of CTO recanalization. Compared to CTO failure patients, all six follow-up variables showed advantage for CTO success patients.